EXPRESSIONISTIC MODEL OF EARLY DRAMATURGY OF YAKOV MAMONTOV - Khorob, S. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the problem of the creative functioning of type expressionism of artistic thought is broken in early dramaturgy (1921-1925) of one of fundamentalists of the Ukrainian dramatic art of ХХ age of Yakov Mamontov. It is led to, that the such modernistic model of his creation was (together with symbolism) not only the sign of the times but also organically swam out from the features of his author aesthetically ideological-beautiful consciousness.